Characterization of aluminum films deposited on silicon substrate by radio frequency (RF) magnetron sputtering - Flauta, Randolph E. (1999)
A study made to determine the characteristics of aluminum thin films deposited on type (lll) silicon (Si) substrate using Radio Frequency (RF) magnetron Sputtering at different operating conditions. The parameters studied include the RF power, deposition time (DT) and operating pressure (OP). The RF power ranged from 75 to 200 Watts. The deposition time ranged from 5 minutes for thin deposits to 2 hours for thicker deposits at varying power and pressure. The operating pressure was set at 5 and 10 mTorr. The minimum ignition pressure was set at 30 mTorr and the base pressure ranged from 4.0 x 10-⁶ to 2.0 x 10-⁵ mTorr.